Institutionalising Design Education and Design Promotion in Australia: From early British influences to wider international engagement - Jackson, Simon (Design and Technology Education: An International Journal, 2016)
Industrial design has grown in Australia from a series of unnamed activities clustered about an emerging 19th century manufacturing industry into a recognised profession. This transformation largely occurred because of the emergence of specific design education and the support offered by professional design associations. Designers working for the early Australian manufacturing industry were given technical education in the areas of engineering, draughtsmanship and foundry work from 1827 onwards in Mechanics’ Institutes. It was from this technical base that the early ‘designers’ working for industry sprang. Technical Schools, Schools of Art and Schools of Mines and Industries all offered training for the designer before industrial design was finally offered as a course of study at tertiary level after WWII. Concurrent with this, professional associations arose to support the emerging industrial design industry in Australia. Nineteenth-century precursors to “modern” design education - Mechanics’ Institutes, Technical Schools, Schools of Art, Schools of Mines and Industries, Junior Technical Schools, Apprenticeships and Secondary School design education - will be surveyed. As with many countries, WWII was a catalysing time for Australian industry as the country geared up production. At the conclusion of hostilities, Australia’s first specific Industrial Design course at tertiary level was born. The purpose of this paper is to show how industrial design activity in Australia has become a profession. An early British lead in both design education and professional design associations was soon broadened to include other international models, as the Australian design industry and Australian society generally, looked to countries other than the ‘mother land’. This paper argues industrial design activity was expanded in every way by the experience of mass-production of goods for the war effort, by new immigrants arriving in this country who often had skills lacking locally, and by the new opportunities offered by the post-war reconstruction programmes. Industrial design was formalised as a profession by industrial design education at tertiary level and the assistance offered to industrial designers by professional associations.